1977
DOI: 10.1111/j.1476-5381.1977.tb08416.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atropine on Acid Secretion Stimulated by Acetylcholine, Histamine and Gastrin in the Isolated Whole Stomach of the Rat

Abstract: An isolated stomach preparation from immature rats has been used to study the effect of atropine on gastric acid secretion. The acid secretory response to acetylcholine was not inhibited by atropine at a concentration of 0.3 μM. Concentrations of atropine of 1 to 3 μM produced a measurable inhibition of acid secretion, and a concentration of atropine of 10 μM caused a complete block of acid secretion which could not be surmounted by high concentrations of acetylcholine. The acid secretory response to histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
2
2
1
Order By: Relevance
“…high concentrations of atropine did not lower basal acid output indicating that the background cholinergic tone in the isolated stomach of the mouse, if at all in existence, is very low. Similar results were found by Bunce et al ( 1977). The H2-receptor antagonists, cimetidine and metiamide in agreement with previous observa tions ( Wan, 1977).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…high concentrations of atropine did not lower basal acid output indicating that the background cholinergic tone in the isolated stomach of the mouse, if at all in existence, is very low. Similar results were found by Bunce et al ( 1977). The H2-receptor antagonists, cimetidine and metiamide in agreement with previous observa tions ( Wan, 1977).…”
Section: Discussionsupporting
confidence: 82%
“…However, it contrasts with the study of Kowalewski and Kolodej (1974) who found that metiamide exhibits some block ing activity at the cholinergic receptor in the isolated canine stomach. High concentrations of atropine did not diminish histamine-induced acid secretion in the isolated stomach, as shown in the present and some previous studies (Bunce et al, 1977;Goto and Watanahe, 1975). All these results under in vitro circumstances are in contrast to those of in vivo studies with dif ferent mammalian species (Lick et al, 1967;Britnblecombe et al 1975;Grossmann and Konturek, 1974).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The concentration ofidazoxan required to antagonize the inhibitory effect of UK-14,304 on acid secretion resulting from field stimulation was substantially greater than those which are effective in other in vitro systems such as guinea-pig ileum and rat vas deferens preparations where concentrations in the range of 40 and 400 nM idazoxan have been used to displace the concentration-response curve for clonidine (Doxey et al, 1983 (Angus & Black, 1979;Bunce et al, 1977). Angus & Black (1979) found that the pKB for atropine when measured against bethanechol-induced acid secretion was significantly lower than in the perfused isolated stomach of the mouse when measured against bethanechol-induced smooth muscle contraction.…”
Section: Resultsmentioning
confidence: 99%